Rethinking welfare and the welfare state - Greve, Bent (Rethinking research and theory series, 2022)
"This innovative book takes a unique approach to rethinking welfare states by considering two centrally interlinked issues: namely what is welfare, and what we should expect from welfare states now and in the future. Bent Greve critically considers thinking on the core elements of welfare states, how they should be ranked and how to recognise indicators of their direction of movement. Providing expert analysis of the historical development of welfare states and the challenges and pressures experienced both regionally and globally, this book argues for a new division of welfare states and a system for balancing old and new social risk. The investigation of dilemmas and the analysis of developing welfare states are particularly illuminating and informative. Greve provides a forward-thinking approach considering long-term stability and the challenges of inequality and poverty in different welfare regimes. He effectively combines new perspectives with attention to a strong public sector economy. With insightful new analysis this book will be an invaluable read for researchers and students of social policy and welfare states"--